The Effectiveness of Flipped Classroom Learning Model Assisted on Padlet Platform in Geography Lessons - M, Indah Fitria; Wijaya, Nyokro Mukti (Universitas Lampung, 2023)
Flipped Classroom Model is a model in which teaching and learning activities are not carried out as usual. Before carrying out learning activities at school, students are given materials to study at home using Padlet platform. The purpose of this study is to see the influence of the use of Flipped Classroom model on the understanding of Atmosphere in Geography lessons. This research uses True Experiment Design with technique Randomized Subject Sampling, Control Group Pre-test Post-test Design. The population in this study were all tenth grade of social science (X IPS) students at Senior High School 2 Dayun, amounting to 68 students, and the sample used is class X IPS 1, amounting to 22 students and X IPS 2 totaling 22 students. The hypothesis test used in this study was the t-test, the results of the study obtained an average post-test score of the experiment class X IPS 2 of 85.54, while the average post-test score of the control class X IPS 1 was 77.00. Based on the data analysis on the t-test, the value of tcount = 6.187 and t table = 1.682. Because tcount is greater than ttable, there is a significant effect of using Flipped Classroom learning model assissted on Padlet Platform.